Pengaruh Tunjangan Kinerja Dinamis dan Kepemimpinan Terhadap Kinerja Pegawai Negeri Sipil - Perdana, Muhammad Ramdhani Putra (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2023)
Dynamic performance allowances and leadership are one of the major factors that can improve the performance of civil servants. The purpose of this study is to determine the benefits of dynamic performance and leadership in influencing the performance of civil servants in Bandung City. The data of this study are Bandung City civil servants in 8 OPDs who have low-performance scores with a population of 2,542. The sampling technique in this study uses a web.raosoft.com sample size with an error rate of 10% so that a sample of 97 respondents is obtained and even 100 respondents. Disseminating questionnaires is a method of data collection. In this work, multiple linear regression analysis is an analysis method. Based on the findings, dynamic performance allowances and leadership have a positive effect on the performance of Bandung City civil servants with a factor of 26.6%, while other factors affect performance by 73.4%. The variable that has a dominant influence is leadership, which is 40.8% influential. The contribution of this study is to expand the literature on human resource management related to performance benefits and leadership in the context of organizations.